Warmer spring conditions increase annual methane emissions from a boreal peat landscape with sporadic permafrost - Manuel Helbig; William L Quinton; Oliver Sonnentag (Environmental Research Letters, 2017)
About a fifth of the global wetland methane emissions originate from boreal peatlands, which represent an important land cover type in boreal landscapes in the sporadic permafrost zone. There, rising air temperatures could lead to warmer spring and longer growing seasons, changing landscape methane emissions. To quantify the effect of warmer spring conditions on methane emissions of a boreal peat landscape in the sporadic permafrost zone of northwestern Canada, we analyzed four years (2013–2016) of methane fluxes measured with the eddy covariance technique and long-term (1951–2016) meteorological observations from a nearby climate station. In May, after snowmelt was complete, mean air temperatures were more than 2 °C warmer in 2013, 2015, and 2016 than in 2014. Mean growing season (May–August) air temperatures, in contrast, differed by less than 1 °C over the four years. Warmer May air temperatures caused earlier wetland soil warming, with temperatures rising from ~0 °C to >12 °C 25 to 40 days earlier and leading to ~6 °C warmer mean soil temperatures between May and June. However, from July to August, soil temperatures were similar among years. Mean May to August and annual methane emissions (6.4 g CH _4 m ^−2 and 9.4 g CH _4  m ^−2 , respectively) of years with warmer spring (i.e. May) temperatures exceeded emissions during the cooler year by 20%–30% (4.5 g CH _4 m ^−2 and 7.2 g CH _4 m ^−2 , respectively). Among years with warmer springs, growing season methane emissions varied little (±0.5 g CH _4 m ^−2 ). The observed interannual differences are most likely caused by a strong soil temperature control on methane fluxes and large soil temperature differences during the spring. Thus, in a warming climate, methane emissions from waterlogged boreal peat landscapes at the southern limit of permafrost are likely to increase in response to more frequent occurrences of warm springs.